2015
DOI: 10.1039/c5cp03769g
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular dynamics simulation study of distribution and dynamics of aqueous solutions of uranyl ions: the effect of varying temperature and concentration

Abstract: Investigating the characteristics of actinyl ions has been of great interest due to their direct relevance in the nuclear fuel cycle. All-atom molecular dynamics simulations have been employed to study the orientational structure and dynamics of aqueous solutions of uranyl ions of various concentrations. The orientational structure of water around a uranyl ion has been thoroughly investigated by calculating different orientational probability distributions corresponding to different molecular axes of water. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
8
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 42 publications
(90 reference statements)
6
8
0
Order By: Relevance
“…Therefore, it can be concluded that both the effects may alter the water diffusivity but in different magnitudes. The reported self-diffusivity of water for the 5U system (2.26 × 10 −9 m 2 /s) 65 is in quantitative agreement with the present simulation results.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Therefore, it can be concluded that both the effects may alter the water diffusivity but in different magnitudes. The reported self-diffusivity of water for the 5U system (2.26 × 10 −9 m 2 /s) 65 is in quantitative agreement with the present simulation results.…”
Section: Resultssupporting
confidence: 90%
“…Similar observation in CN was also reported by Chopra and Choudhury. 65 The predominant monodentate binding mode was observed in an aqueous environment using Raman spectroscopy by Brooker et al and Nguyenttung et al 70,71 Again, Chiarizia and co-workers also established the monodentate structure in a water-rich medium using extended X-ray absorption fine structure measurements. 72 According to the work of Buḧl et al, the solvent effect facilitated the transition from bidentate to monodentate and the nitrate ions are rather involved in intermolecular HBs with the solvent instead of intramolecular HBs with uranyl water.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations